Description of nature as an act of anticipation: Australia in Rosa Campbell Praed’s My Australian Girlhood - Klepač, Tihana (2010)
Writing My Australian Girlhood from the position of her “civilised existence” in 1902 London Rosa Campbell Praed remembers her “wild youth ‘down under.’” In line with the dominant discourses of the period Praed describes Australia as a “young-old land”, and additionally associates it with nature which stands in sharp opposition to culture, to “the smug English conventionalities.” Her images of nature progress from “the grim spell of the bush, ” which overwhelms the traveller into the impenetrable “primeval forests” of Australia, via the slopes of the lush rose garden with vines along its fences, to the brown, scorched grass, and dry creeks under the “steaming grey blanket” of intense summer heat, and the “flaming scorpions of fires” racing down the mountains, thus providing emotional sustenance required to create a home in an unknown land. As such Praed’s text is a “protest against the direct actions of [her] masculine counterparts” who were involved in the process of taming of the wilderness identifying the clearing of the land as a preparation for its “true possession” once it is “remade in a more familiar image” (Holmes, Martin and Mirmohamadi).
Projekt MZOS
ENG